A Paradigm for Post-Covid-19 Fatigue Syndrome Analogous to ME/CFS - Mackay, Angus (Frontiers in Neurology, 2021)
A significant proportion of COVID-19 patients are suffering from prolonged Post-COVID-19 Fatigue Syndrome, with characteristics typically found in Myalgic Encephalomyelitis/ Chronic Fatigue Syndrome (ME/CFS). However, no clear pathophysiological explanation, as yet, has been provided. A novel paradigm for a Post-COVID-19 Fatigue Syndrome is developed here from a recent unifying model for ME/CFS. Central to its rationale, SARS-CoV-2, in common with the triggers (viral and non-viral) of ME/CFS, is proposed to be a physiologically severe stressor, which could be targeting a stress-integrator, within the brain: the hypothalamic paraventricular nucleus (PVN). It is proposed that inflammatory mediators, released at the site of COVID-19 infection, would be transmitted as stress-signals, via humoral and neural pathways, which overwhelm this stress-centre. In genetically susceptible people, an intrinsic stress-threshold is suggested to be exceeded causing ongoing dysfunction to the hypothalamic PVN’s complex neurological circuitry. In this compromised state, the hypothalamic PVN might then be hyper-sensitive to a wide range of life’s ongoing physiological stressors. This could result in the reported post-exertional malaise episodes and more severe relapses, in common with ME/CFS, that perpetuate an ongoing disease state. When a certain stress-tolerance-level is exceeded, the hypothalamic PVN can become an epicentre for microglia-induced activation and neuroinflammation, affecting the hypothalamus and its proximal limbic system, which would account for the range of reported ME/CFS-like symptoms. A model for Post-COVID-19 Fatigue Syndrome is provided to stimulate discussion and critical evaluation. Brain-scanning studies, incorporating increasingly sophisticated imaging technology should enable chronic neuroinflammation to be detected, even at a low level, in the finite detail required, thus helping to test this model, while advancing our understanding of Post-COVID-19 Fatigue Syndrome pathophysiology.